Metal organic framework based PVDF separators for high rate cycling lithium-ion batteries - Valverde, Ainara (2020)
Poly(vinylidene fluoride) (PVDF) and MOF-808-based separators for lithium-ion batteries (LIBs) have been prepared and fully characterized in terms of morphological and thermal properties, electrolyte uptake, and retention, and surface hydrophilic characteristics. The effect of PVDF/MOF-808 separators on the electrochemical performance of LIBs has been evaluated. The PVDF/MOF-808 membranes exhibit a well-defined porous structure with a uniform distribution of interconnected macro- to mesopores. The inclusion of the Zr-based MOF nanoparticles increases the porosity and surface area of the separator, enhancing the electrolyte uptake and the ionic conductivity. Finally, the presence of MOF-808 fillers improves the liquid electrolyte retention, which prevents the capacity fading at high C-rates cycling. Indeed, charge–discharge tests performed in Li/C-LiFePO4 half-cells reveal a discharge capacity of 68 mAh·.g–1 at 2C-rate for PVDF/MOF-808 membranes, in comparison with the 0 mAh·g–1 obtained for pure PVDF. The PVDF/10 wt % MOF-808 sample shows a long-term stable cycling behavior with a Coulombic efficiency close to 100%. Thus, it is shown that the composite membranes represent an improvement with respect to conventional separators for lithium ion battery applications, since they coupled the polymer meso- and macroporous structure with the well-ordered microporous system of the MOFs, which improve significantly the electrolyte affinity